2018
DOI: 10.3390/ijerph15092051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accessibility of Healthcare Facilities Using an Integrated Catchment Area Approach

Abstract: Accessibility is a major method for evaluating the distribution of service facilities and identifying areas in shortage of service. Traditional accessibility methods, however, are largely model-based and do not consider the actual utilization of services, which may lead to results that are different from those obtained when people’s actual behaviors are taken into account. Based on taxi GPS trajectory data, this paper proposed a novel integrated catchment area (ICA) that integrates actual human travel behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Our direct observation of the studied area revealed that the community have easy access to nearby facilities and free medical services provided by government-run healthcare facilities. This suggests a good availability of health services and the accessibility of healthcare facilities in the study region (22). However, a small proportion of respondents still practice selfmedication procured from the nearby sundry shop as well as observed traditional healing methods.…”
Section: Discussionmentioning
confidence: 87%
“…Our direct observation of the studied area revealed that the community have easy access to nearby facilities and free medical services provided by government-run healthcare facilities. This suggests a good availability of health services and the accessibility of healthcare facilities in the study region (22). However, a small proportion of respondents still practice selfmedication procured from the nearby sundry shop as well as observed traditional healing methods.…”
Section: Discussionmentioning
confidence: 87%
“…Theoretical reachability probability is a reachability probability model that is based on the spatial distance threshold [55,56]. Ingram proposed a reachability model and suggested that if the distance from a specific location to a service facility is the shortest, then the probability of reaching that location is the highest [57].…”
Section: Accessibility Possibility Modelmentioning
confidence: 99%
“…. , l 21 }, b i is the arbitrary position grid in B, and l j is the maximum departure (O point) area of a specific lake in L, then starting from the position grid l j , the distance-based theoretical reachability probability D of the position grid of b i can be expressed as [55]…”
Section: Accessibility Possibility Modelmentioning
confidence: 99%
“…Enhanced two steps floating catchment area method come to overcome the rigidity and arbitrariness of the 2SFCA i.e. it does not take into account the distance decay method, it sets catchment and subzones of healthcare by considering travel time or travel distance based on the road network is often used as the spatial barrier or impedance [19]. Three steps floating catchment area method used by Rekha et al [1] to calculate accessibility by considering three attributes namely attractiveness of health services, travel time and distance between the location of the service centre and the location of residents and population demand for healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%